Actinide arene-metalates: 2. A neutral uranium bis(anthracenide) sandwich complex and elucidation of its electronic structure. Issue 65 (26th July 2022) - Murillo, Jesse; Bhowmick, Rina; Harriman, Katie L. M.; Gomez-Torres, Alejandra; Wright, Joshua; Miró, Pere; Metta-Magaña, Alejandro; Murugesu, Muralee; Vlaisavljevich, Bess; Fortier, Skye
Abstract : Reaction of [UI2 (HMPA)4 ]I with potassium anthracenide gives the unprecedented arenide-sandwich complex U(η 6 -C14 H10 )(η 4 -C14 H10 )(HMPA)2 . CASSCF calculations indicate the U–C bonding to solely consist of π-interactions. Abstract : An unprecedented sandwich complex of the actinides is synthesized from the treatment of [UI2 (HMPA)4 ]I (HMPA = OP(NMe2 )3 ) (2 ) with 3 equiv. of K(C14 H10 ) to give the neutral, bis(arenide) species U(η 6 -C14 H10 )(η 4 -C14 H10 )(HMPA)2 (1 ). Solid-state X-ray, SQUID magnetometry, and XANES analyses are consistent with tetravalent uranium supported by [C14 H10 ] 2− ligands. In one case, treatment of 1 with an equiv. of AgOTf led to the isolation of U(η 6 -C14 H10 )2 (HMPA)(THF) (3 ), formed from ring migration and haptotropic rearrangement. Complete active space (CASSCF) calculations indicate the U–C bonding to solely consist of π-interactions, presenting a unique electronic structure distinct from classic actinide sandwich compounds.